Keterbatasan Lahan Hunian Di Kawasan Perkotaan Dalam Cerpen Hunian Ternyaman Karya Lamia Putri Damayanti - Elisha Diani Nurmalitasari; Alfaza Kesit Herda Kumara; Eva Dwi Kurniawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The short story “Hunian Ternyaman” was chosen by the author because it conveys several dilemmas of limited residential land felt by people living in urban areas. This study aims to examine how limited land is felt by people in urban areas which then causes various problems that interfere with the quality of life and comfort of people living in urban areas. The formulation of this research problem is (1) How the role of housing on the survival of the community, (2) What are the problems that cause limited land in urban areas, (3) What are the impacts caused by the problems that occur. The use of methods in this study is descriptive qualitative that displays data as it is without data manipulation with a hermeneutic approach. The result of this study is that the high need for housing that occurs in urban areas accelerates the development process but causes many problems so that development planning is needed to ensure sustainability and a good quality of life for residents.